The Correlation of Means and Infrastructure Standards on Student Achievement - Ari Fuazi; Jailani; Saifullah (Winaya Inspirasi Nusantara Foundation, 2020)
A specific educational institution requires the assistance of suitable infrastructure and educational facilities. Because the infrastructure and facilities for good learning will make the process of teaching and learning more successful and effective. However, not all academic institutions have top-notch infrastructure and amenities. A Pesantren with sufficient infrastructure and facilities is Pesantren Sulaimaniyah. Pesantren Nurul Awal, on the other hand, is a Pesantren that lacks the necessary infrastructure and facilities. As a result, this thesis explores the relationship between students' academic success and the quality of facilities and infrastructure. This study intends to provide an answer to the following question: (1) How do amenities and infrastructure affect student achievement? (2) Does the kid perform better academically at Pesantren Sulaimaniyah than at Nurul Awal Pesantren? While